Correlação entre variáveis meteorológicas e focos ativos para o Rio Grande do Norte - Brito, Bruno Menezes Nogueira (Universidade Federal Rural do Semi-Árido, 2021)
Hotspots are locations that have reached temperatures above 47 ºC and can originate from controlled burns and forest fires. These data are registered by satellites and are the main means for estimating forest fires in the country. This work aims to analyze the occurrence of hotspots in Rio Grande do Norte, Brazil, analyze the meteorological variables temperature, wind speed, relative humidity, and precipitation, in the period from 1999 to 2019, evaluate the correlation between the variables and the hotspots for the state and define which are the months of greatest risk of forest fires. The hotspots data were obtained from the National Institute for Space Research (INPE) and the climatological data from the National Institute of Meteorology (INMET). The results indicate that there is significant correlation between meteorological variables and the occurrence of hotspots. Hotspots and temperature increased during the period studied, while wind speed, precipitation and relative humidity decreased. The months with the most favorable environmental conditions for forest fires are October, November and December, and the period with the lowest probability of occurrence is from March to July, since it is the rainy season. The months recommended for controlled burns are January and July
Keywords: Focos ativos; Queimada controlada; Prevenção aos incêndios florestais; Hotspots; Controlled burns; Forest fire prevention; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL